A Current-mode Logarithmic Function Circuit - Muhammad Taher Abuelma'atti; Osama Oglah Faris (Active and Passive Electronic Components)
A new current-mode analog circuit configuration that implements the function ln (x/y) is proposed. The circuit uses bipolar transistors and resistors and is suitable for integration. In the proposed circuit the ratio (x/y) can be larger or smaller than unity. Simulation results are included.